The extraordinary life story of Ivan Vasilievich Krivonogov: from an ordinary doctor to a deputy of the State Duma - A. E. Moseev; I. M. Kobelev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
The history of medicine is written not only by bright events in the medical field, new discoveries and innovations, but also by the people who create these events. One of the worthy representatives of the medical field of activity is Ivan Vasilyevich Krivonogov. Covering the history of his life and work during the existence of the Russian Empire is a pressing task against the background of the emergence of new, previously unknown facts of the doctor's biography. The purpose of this study was to clarify some facts from the life of Doctor of Medicine Ivan Vasilyevich Krivonogov, to search for previously unknown biographical data. The methodological basis of the study was a systematic approach based on the principles of historicism, objectivity and scientificity, as well as general scientific methods (generalization, analysis, synthesis, induction). The materials for the study were documents from the State Archives of the Arkhangelsk Region, newspaper articles, book publications, documents of the electronic library of the State Public Historical Library, scientific articles, etc. Ivan Vasilyevich came from a merchant family, his father traded in consumer goods in Arkhangelsk. He successfully graduated from the Imperial Military Medical Academy in St. Petersburg in 1891, after which he devoted his entire life to medicine. In 1896, physician Krivonogov defended his dissertation, becoming a doctor of medicine. From 1896, he worked as a junior and then senior physician of the Special White Sea Department of the Border Guard, and lived in Arkhangelsk. During the Russo-Japanese War, he was a physician, and then the head of the hospital for the reception of the wounded and sick from the Far East, created in response to a request for help from the Grand Duchesses Maria Pavlovna and Ksenia Alexandrovna. He was one of the founders of the Arkhangelsk Society for the Study of the Russian North (1908), and a co-founder of the Arkhangelsk Photographic Society (1909). Ivan Vasilyevich headed the Society of Arkhangelsk Physicians from 1913 and was in charge of the society's hospital. On December 10 (23), 1913, in the byelections, Krivonogov I. V. was elected to the IV State Duma from the first and second congresses of city voters, where he joined the progressive faction. Undoubtedly, the presented data significantly supplement the biography of the doctor known to date, who became part of the history of medicine and whose memory should be honored by his grateful descendants.